2013
DOI: 10.1002/pon.3384
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of young patients with breast cancer toward fertility loss related to adjuvant systemic therapies. EORTC study 10002 BIG 3‐98

Abstract: For the majority of young patients with breast cancer, cure remains their first priority; for this, they are willing to accept a considerable decrease in future fertility, and only less than 10% will forego chances of cure to preserve fertility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(80 citation statements)
references
References 28 publications
1
76
0
3
Order By: Relevance
“…Among a substantial number of younger women with breast cancer, the likelihood of infertility after chemotherapy treatment, and/or the delay in potential attempts at pregnancy due to 5 years of tamoxifen therapy is a signifi cant concern (Senkus et al 2014 ;Partridge et al 2004 ). Young women's attitudes are most infl uenced by whether or not they have already had children, as well as their desire to have future children.…”
Section: Fertility Preservation: Practice and Researchmentioning
confidence: 99%
“…Among a substantial number of younger women with breast cancer, the likelihood of infertility after chemotherapy treatment, and/or the delay in potential attempts at pregnancy due to 5 years of tamoxifen therapy is a signifi cant concern (Senkus et al 2014 ;Partridge et al 2004 ). Young women's attitudes are most infl uenced by whether or not they have already had children, as well as their desire to have future children.…”
Section: Fertility Preservation: Practice and Researchmentioning
confidence: 99%
“…In addition, few data are reported related to cognitive impairment associated with the use of hormonal and chemotherapy treatment, which can be particularly problematic for the continuation of professional and family-related plans of young women. A European Organization for Research and Treatment of Cancer study about fertility attitudes in young BC women, which included 12% of patients from South America (Peru and Chile), showed that Latin American patients required an increase in the chance of being cured to accept chemotherapy with potential fertility loss and were less likely to accept higher infertility rates than women from the Middle East and Western and Eastern Europe [47].…”
Section: Bc In Young Women: Special Considerationsmentioning
confidence: 99%
“…The majority of patients with a current desire to have children decided against a pregnancy because they were afraid of cancer-related effects, such as shortened life expectancy or a negative impact of a pregnancy on BC prognosis. In the study by Ruddy et al [20] analyzing 600 women with BC, 9% of those with maternal desire did not plan a pregnancy because they were afraid of cancer recurrence, while the BIG 3-98 study reported that 40% of women did not fulfill their desire to have children due to this anxiety [21]. In our cohort, only 21.7% of those patients with a desire for motherhood decided to have more children after BC diagnosis.…”
Section: Reproductive Concernsmentioning
confidence: 58%